Explorando a diversidade genética e taxonômica no grupo extended Asfarviridae: Um estudo de genômica comparativa - Thiago Mendonça dos Santos (2024)
The giant virus family Asfarviridae officially encompasses only species of the genus Asfivirus, however, a genetic association with other viruses such as Faustovirus, Kaumoebavirus, Pacmanvirus, and Abalone asfar-like virus has been observed, thus forming the <extended Asfarviridae= group. Despite the genetic association, there is a lack of consensus on classifying these viruses as a cohesive taxon. This work aims to investigate the genomic diversity and taxonomy of viruses in the extended Asfarviridae group. The adopted methodology included a detailed analysis of the genomic characteristics of these viruses, including genome size, predicted protein count, and G+C content, as well as average amino acid (AAI) and nucleotide (ANI) identities, commonly used in viral taxonomy. Additionally, a study of the extended Asfarviridae group's pangenome was conducted by clustering protein sequences into orthologous groups. Furthermore, the open or closed nature of the genome was investigated, along with the identification of core and accessory genes. Phylogenetic analysis, performed through Maximum Likelihood, allowed the construction of a phylogenetic tree based on core genes, providing insights into the evolutionary relationship between these viruses. The investigation of gene collinearity preservation among different virus groups was also conducted. The obtained results revealed considerable genomic diversity within the extended Asfarviridae group, contrasting with the expected uniformity among members of the same taxon. This diversity is manifested in significant genome differences, both in terms of size and G+C content. The extended Asfarviridae pangenome demonstrated to be open, with a restricted core of 37 genes and a broad accessory genome. Additionally, variations in amino acid and nucleotide identity were observed among members of this group, indicating wide genetic diversity. Furthermore, a lack of conservation in gene order among these viruses was identified. Based on the obtained results, together with phenotypic data, a revision in the taxonomy of these viruses is proposed, no longer grouping them into a single family. Therefore, the possible separation of Faustovirus and Asfivirus, Kaumoebavirus and Pacmanvirus into multiple distinct species is suggested. These findings emphasize the ongoing need for research for a more precise understanding of giant virus genetic and evolutionary diversity, as well as their taxonomic and biological implications.